Solar irradiance and efficient use of energy: Residential construction toward net-zero energy building. (October 2022) - Almutairi, Khalid; Aungkulanon, Pasura; Algarni, Salem; Alqahtani, Talal; Keshuov, Seitkazy A.
Abstract: The feasibility of implementing zero energy buildings in Muscat, Sultanate of Oman, was investigated in this study. To determine potential points in the region, raw climatic data from meteorological stations in and around the region were first received, and after counting, sorting, and reconstruction, climate maps in the region were created. Surfaces were chosen based on which received the most solar energy, and the optimal point was chosen based on a field study of topographic conditions. Then, special design elements such as thermal insulation, thermal inertia reduction, canopy, building facade, and spatial orientation were considered. The average amount of current consumption per day (ICD) was used to calculate the number of solar panels, and calculations for The results showed that the amount of energy received from the sun in one square meter during one year, according to the optimal position of solar cells in the Muscat climate from the Solar Radiation model, is approximately equal to 1710 kWh. The final result of the modeling is a building with a total area of 290 m2. Calculating the annual energy consumption and electricity consumption yielded a total consumption of 25, 200 kWh per year and a production of 19, 900 kWh per year. It is proposed that this energy shortage be met by installing 23 m2 of PV panels as canopies at a rate of 61000kWh per year.